People-centred development in practice: the case of the Zikhova-Ngqinisa Sidibene Woodlot Trust Project - Pona, Faith Zolisa (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2003)
This study addresses the question of people-centred development as a transformative aspect of the new South African development arena. The concept is defined as the involvement and active participation of people in the decision-making, evaluation and implementation of the development processes, It is one of the forms of democratisation which involves the decentralisaton of authority to the lower tiers of government. This study provides an analysis of the efficacy, relevance, advantages and disadvantages of people-centred development in the South African context. The Zikhoya-Ngqinisa Woodlot Trust Project was chosen as a case study, The reason was that through the process of devolution of the Department of Forestry and Water Affairs (DWAF), which involved the handing over of the management and financial resources of the small woodlots to the communities for their own benefit, the two villages, Zikhova and Ngqinisa, were given the Zikhova woodlot. The devolution of DWAF is one of the various forms of decentralisation that has given more autonomy to the lower tiers of government in the sense that the communities now have to satisfy their own needs. The main focus of the study was to identify and analyse constraints on the implementation of people-centred development specific to the Zikhova-Ngqinisa Woodlot Trust Project. Other interrelated aspects of people-centred development such as sustainability, community involvement and benefits of the project were also investigated and analysed.,KMBT_363
Keywords: Zikhova-Ngqinisa Sidibene Woodlot Trust Project; Rural development -- South Africa -- Eastern Cape; Rural development projects -- South Africa -- Eastern Cape -- Citizen participation; Woodlots -- South Africa -- Eastern Cape; Economic development projects -- South Africa -- Eastern Cape